2015
DOI: 10.1039/c5tb00046g
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of demineralized bone matrix powder using a salt-leached silk fibroin carrier for bone regeneration

Abstract: Demineralized bone matrix (DBM) has been widely used for bone regeneration due to its osteoinductivity and osteoconductivity. However, the use of DBM powder is limited due to the difficulties in handling, the tendency to migrate from graft sites and the lack of stability after surgery. In this study, a mechanically stable, salt-leached porous silk fibroin carrier was used to improve the handling properties of DBM powder and to support the attachment, proliferation and osteogenic differentiation of rat bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Though no specific, isolated biological agents inducing osteogenic differentiation, such as plasmid DNA, PDGF, or BMP‐2, were added in this study, DBM has been shown to retain some BMP proteins and collagens (Wildemann, Kadow‐Romacker, Haas, & Schmidmaier, ). For prior studies in the rat model with DBM inclusion (Ding et al, ; Dozza et al, ), correlations between osteogenic gene expression and ALP/calcium deposition have shown, specifically that DBM was associated with osteogenic gene expression, including COL1A1, ALP, OCN, and ONN. The effect of adding Mg to the polymer/DBM scaffold is consistent with earlier reports with Mg‐containing materials (Liu et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Though no specific, isolated biological agents inducing osteogenic differentiation, such as plasmid DNA, PDGF, or BMP‐2, were added in this study, DBM has been shown to retain some BMP proteins and collagens (Wildemann, Kadow‐Romacker, Haas, & Schmidmaier, ). For prior studies in the rat model with DBM inclusion (Ding et al, ; Dozza et al, ), correlations between osteogenic gene expression and ALP/calcium deposition have shown, specifically that DBM was associated with osteogenic gene expression, including COL1A1, ALP, OCN, and ONN. The effect of adding Mg to the polymer/DBM scaffold is consistent with earlier reports with Mg‐containing materials (Liu et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…The rotating target holding the Mg mesh ensured the Mg mesh was encapsulated by the PLGA fibres (as shown in Figure c) as well as DBM particles being distributed into the scaffold. It has been shown that the loading strategy of DBM into composite materials can have a large effect on the delivery and release of its bioactive components and thus the resulting bone regenerative efficacy (Ding et al, ). In this study, viscous hyaluronic acid (HA) was used to suspend DBM particles, which made the electrospraying process easier to accomplish.…”
Section: Discussionmentioning
confidence: 99%
“…A salt-leached 3D porous SF scaffold was produced to improve the characteristics of DBM powders and to enhance the adhesion, proliferation, and osteoblastic differentiation of BMSCs. 59 …”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…To address these requirements, conventional fabrication methods and solid freeform fabrication (SFF) methods have been developed. There are various conventional methods for preparing scaffolds, including salt‐leaching, gas‐forming, solvent‐casting (SC), phase separation, and freeze‐drying techniques . Similarly, SFF methods encompass a wide range of procedures, including the use of a stereo lithography apparatus, selective laser sintering, and three dimensional (3D) plotting .…”
Section: Introductionmentioning
confidence: 99%
“…There are various conventional methods for preparing scaffolds, including salt-leaching, gas-forming, solvent-casting (SC), phase separation, and freeze-drying techniques. [11][12][13][14][15] Similarly, SFF methods encompass a wide range of procedures, including the use of a stereo lithography apparatus, selective laser sintering, and three dimensional (3D) plotting. [16][17][18] Commonly, SFF techniques can be used to fabricate scaffolds with well-defined pore structures and interconnected pores compared with conventional methods.…”
Section: Introductionmentioning
confidence: 99%